Integrating environmental management systems into tourism industry operations: challenges and strategic approaches - Steiva Amerlien Sandra Wowiling; Herdianto Lantemona (Lentera Negeri, 2026)
This study explores the integration of Environmental Management Systems (EMS) into tourism industry operations, focusing on the challenges faced and strategic approaches employed to overcome them. Utilizing a qualitative research method through an extensive literature review and library research, this paper synthesizes existing knowledge on EMS adoption within tourism sectors globally. The tourism industry, while a significant economic contributor, poses considerable environmental risks due to resource consumption, waste generation, and ecosystem disruption. EMS offers a structured framework to mitigate these impacts by coordinating policies, responsibilities, and operational procedures aimed at sustainability. However, the implementation of EMS in tourism is hindered by factors such as limited environmental awareness, financial constraints, and resistance to organizational change. The literature reveals that successful EMS integration requires strategic approaches including stakeholder engagement, continuous innovation, capacity building, and transparent communication. Furthermore, the role of local communities, government regulations, and private sector commitment emerges as critical in fostering effective EMS adoption. The findings underscore that EMS not only enhances environmental performance but also contributes to competitive advantage by aligning tourism operations with global sustainability standards. This research contributes to a deeper understanding of the complexities in EMS implementation in tourism and offers practical insights for policymakers, industry practitioners, and researchers aiming to promote sustainable tourism development. Future research directions include empirical studies on EMS impact assessment and the development of tailored EMS models for diverse tourism contexts.